Current treatment options for postmenopausal vaginal atrophy - Naumova I; Castelo-Branco C (Dove Medical Press, 2018)
Iuliia Naumova,1 Camil Castelo-Branco2 1Department of Obstetrics and Gynecology, Faculty of General Medicine Saratov State Medical University named after V.I. Razumovsky, Saratov, Russia; 2Institute Clinic of Gynecology, Obstetrics and Neonatology, Faculty of Medicine-University of Barcelona, Hospital Clinic-August Pi i Sunyer Biomedical Research Institute (IDIBAPS), Barcelona, Spain Abstract: Vulvovaginal atrophy (VVA) is a silent epidemic that affects up to 50%–60% of postmenopausal women who are suffering in silence from this condition. Hormonal changes, especially hypoestrogenism inherent in menopause, are characterized by a variety of symptoms. More than half of menopausal women are concerned about the symptoms of VVA, such as dryness, burning, itching, vaginal discomfort, pain and burning when urinating, dyspareunia, and spotting during intercourse. All these manifestations significantly reduce the quality of life and cause discomfort in the sexual sphere. However, according to research, only 25% of patients with the symptoms of VVA receive adequate therapy. This is probably due to the lack of coverage of this problem in the society and the insufficiently active position of specialists in the field of women’s health regarding the detection of symptoms of VVA. Many patients are embarrassed to discuss intimate complaints with a specialist, which makes it difficult to verify the diagnosis in 75% of cases, and some patients regard the symptoms of VVA as manifestations of the natural aging process and do not seek help. Modern medicine has in the arsenal various options for treating this pathological condition, including systemic and topical hormone replacement therapy, the use of selective estrogen receptor modulators, vaginal dehydroepiandrosterone, use of lubricants and moisturizers, as well as non-drug therapies. Timely diagnosis and adequately selected therapy for the main symptoms of VVA lead to restoration and maintenance of the vaginal function and vaginal health. Keywords: vulvovaginal atrophy, vaginal dryness, dyspareunia, menopause, hormonal replacement therapy, local estrogen, selective estrogen receptor modulator, vaginal dehydroepiandrosterone